2021
DOI: 10.15252/embj.2020105912
|View full text |Cite
|
Sign up to set email alerts
|

An organoid‐derived bronchioalveolar model for SARS‐CoV‐2 infection of human alveolar type II‐like cells

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) causes coronavirus disease 2019 (COVID‐19), which may result in acute respiratory distress syndrome (ARDS), multiorgan failure, and death. The alveolar epithelium is a major target of the virus, but representative models to study virus host interactions in more detail are currently lacking. Here, we describe a human 2D air–liquid interface culture system which was characterized by confocal and electron microscopy and single‐cell mRNA expression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(177 citation statements)
references
References 74 publications
4
159
1
2
Order By: Relevance
“…The abundant ACE2 expression in Calu-3 cells is therefore in accordance with a previous study that showed the ACE2 gene is highly expressed in lung ciliated cells [18] . In addition, the single-cell RNA sequencing study indicated that ACE2 is expressed at low levels in the alveolar cluster of organoid-derived bronchioalveolar-like cultures [21] . This finding is in accordance with our observation of relatively low but detectable ACE2 protein levels in H322M cells, which were derived from a primary bronchioalveolar carcinoma of the lung [22] .…”
Section: Discussionmentioning
confidence: 99%
“…The abundant ACE2 expression in Calu-3 cells is therefore in accordance with a previous study that showed the ACE2 gene is highly expressed in lung ciliated cells [18] . In addition, the single-cell RNA sequencing study indicated that ACE2 is expressed at low levels in the alveolar cluster of organoid-derived bronchioalveolar-like cultures [21] . This finding is in accordance with our observation of relatively low but detectable ACE2 protein levels in H322M cells, which were derived from a primary bronchioalveolar carcinoma of the lung [22] .…”
Section: Discussionmentioning
confidence: 99%
“…A more heterogeneous cellular composition has been achieved by differentiating fetal lung-derived SOX2 + SOX9 + bud tip progenitor cell organoids in 2D ALI cultures. They comprise alveolar-like and bronchiallike cell types and are readily infected by SARS-CoV-2 (254). However, this model meets similar limitations as hPSC-derived alveolar models due to the limited access to donor material and the derivation of differentiated bronchioalveolar ALI cultures from few organoid lines.…”
Section: Modeling Sars-cov-2 Infection and Pathogenesis In The Respiratory Tractmentioning
confidence: 99%
“…SARS-CoV-2 affects several organs causing severe damage of the lung; cardiovascular, intestinal, and neurological, and endothelial systems; kidney; and liver, showing direct effects on these tissues. Recent studies showed that human bronchial, lung, kidney, liver, intestinal, and vascular organoids are all permissive to SARS-CoV-2 and may represent viral reservoir [78][79][80][81][82][83][84]. Antiviral effects of COVID-19 candidate therapeutic compounds have been evaluated in organoid systems [85][86][87][88].…”
Section: Cell-based Approachesmentioning
confidence: 99%